Entrapment of the small intestine in the epiploic foramen in crib-biting horses: case report - Alonso, J. M. [UNESP]; Watanabe, M. J. [UNESP]; Rodrigues, C. A. [UNESP]; Alves, A. L. G. [UNESP]; Ramos, C. M. [UNESP]; Rosa, G. S. [UNESP]; Hussni, C. A. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
Four cases of epiploic foramen entrapment (EFE) are reported. Among the cases, three males and one female, two Quarter Horses, one mixed breed and one Brazilian Equestrian, aged between 3 to 20 years, mean 11 years. The average height was 160.5cm and 465kg. All horses had a previous record of crib-biting habit. The presence of enterogastric reflux and small intestine distended loops in transrectal palpation was variable in dependence of the trapped segment. In surgical exploration were identified two cases of jejunum and ileum entrapped, one of the ileum and one of jejunum. All animals showed EFE from left to right. The horse that had trapped the ileum has survived. The others were euthanized due to the extent of injury or rupture of large vessels during surgical reduction. Although there are many notes of possible risk factors for EFE occurrence, cribbing is the risk factor that has the highest positive correlation with EFE. This appointment was confirmed by the cases presented. Despite being described a good prognosis for the EFE, a bad outcome was achieved among the cases, and stresses that the extent of the injury and bleeding from the portal vein contributed to this outcome.
Keywords: colic; cribbing; epiploic foramen; horses